Effect of cumulus-oocyte complexes (COCs) culture duration on IN VITRO maturation and parthenogenetic development of pig oocyte - Zai-Dong Hua; Xin-Min Zheng; Qing-Xin Wei; Hou-Qiang Xu; Ya-Gang Wang; XiMei Liu,Li Li,Hong-Wei Xiao; Xian-Feng Qiao (African Journal of Pig Farming, 2018)
We investigated and optimized the cumulus-oocyte complexes (COCs) culture duration for pig oocyte IN VITRO maturation and produced a number of high-quality metaphase-II (M-II) oocytes for generation of parthenotes. The present study graded the COCs into levels A, B and C according to layers of cumulus cells, which were cultured IN VITRO for 24, 32, 38, 44, 48 and 54 h, respectively. Subsequently, the oocytes with extruded polar body at different time point were electrically activated. The rates of cleavage and blastocyst formation were assessed on day 2 and 7, respectively. The maturation rates of COCs of both level A and B arrived at the highest point at 44 to 48 h, which were statistically insignificant (P > 0.05), while level C COCs needed longer maturation time (54 h), for most of the oocytes to become mature. COCs of different levels were cultured IN VITRO for the same term, the maturation rates of levels A and B were not significantly different (P > 0.05), but both were significantly higher (P < 0.05) than that of level C. After parthenogenetic activation, there were no significant differences between the cleavage rates in the groups of 38 to 54 h maturation duration, whereas the developmental rate to blastocysts after 44 h (16.1%) and 48 h (16.5%) maturation duration were significantly higher than those from the other term groups (0, 2.2, 9.8 and 12.4% for 24, 32, 38 and 54 h, respectively, P < 0.05). COCs of levels A and B were more suitable for oocytes preparation IN VITRO, which led to a high maturation rate: 44 to 48 h duration was beneficial for maturation, cleavage and blastocyst formation. As for 38 h or less maturation duration, rates of blastocyst were extremely low although some oocytes could be seen with the polar body and cleaved to some extent (64.5% for 3 8h IVM), indicating that oocytes were not really matured. Therefore, the developmental maturation of oocytes could not be judged only by excluding the first polar body.